Effects of adding high- vs low-intensity resistance training to endurance training in patients with heart failure: preliminary results of a randomized controlled trial. (3rd October 2022) - Gojevic, T; Turri Da Silva, N; Gelade, K; Jacobs, G; Pirlotte, R; Tulleneers, B; Duchateau, A; Mullens, W; Hansen, D
Abstract: Background: In current ESC/EAPC guidelines, adding resistance training to endurance training is advised for patients with heart failure (HF), but the optimal intensity of the resistance training is unknown (40–80% of 1RM is advised). Purpose: To investigate the effects of high- vs low-intensity resistance training as an adjunct to endurance training on: aerobic capacity (primary outcome), walking capacity, muscle strength and quality of life in patients with HF. Methods: Forty patients with HF were consecutively recruited in the cardiac rehabilitation center of the Hospital East-Limburg in Belgium. Patients were block-randomized (by age and sex) by an independent researcher to receive maximally 45 supervised sessions (3x/week) of high-intense (HI: 3 exercises, 3x12 repetitions, 55–70%1RM) or low-intense resistance training (LI: 3 exercises, 3x22 repetitions, 35–40%1RM) as an adjunct to endurance training (30 min/session; 50–75% VO2max). The aerobic capacity (VO2max) was measured by a blinded assessor with a ramp cardiopulmonary cycling test (+5–30W/min). Walking distance was assessed with a 6-minute walk test (6MWT), maximal strength with 1RM (leg-press, pull-down and dip), and quality of life with the Minnesota questionnaire. An unpaired t-test, Mann-Whitney U test or ANCOVA were used for between-group analysis, and paired t-test or Wilcox sign-rank test for the within-group analysis. Results: Both groups had similar baseline characteristics and training adherence (HI vs LI; 20 vs 20 subjects; Age: 62±9 vs 59±13 years; Sex: 76% vs 79%male; BMI: 27±58 vs 29±4 kg/m 2 ; LVEF: 35±10 vs 38±6%; Adherence: 33±10 vs 36±10 sessions; p>0.05). There were no adverse events. Both groups had significant within-group improvements in aerobic and walking capacity (VO2max: LI (n=20) vs HI (n=19), p≤0.010; 6MWT distance: p≤0.007) (Figure 1), but these improvements did not differ between groups (VO2max: p=0.855; 6MWT distance: p=0.854). The LI group improved significantly more in muscle strength than the HI group (dip and leg-press: p<0.001). Although the LI group significantly improved in the quality of life (Minnesota score reduction: p=0.028), the quality of life did not differ between groups (Minnesota score: p=0.756). Conclusions: Both low-and high-intense resistance training are similarly beneficial for improving aerobic and walking capacity in patients with HF. Surprisingly, low-intense resistance training seems superior to high-intense training in improving muscle strength. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Hasselt University